Technical Paper Proposed Performance Management Framework - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The BC agriculture sector is an important contributor to the economy, with $2.9 billion in farm cash receipts in 2014. The sector is highly diverse, due to BC’s varied topography and climate conditions. The agricultural land base is small, comprising about five percent of the province. Climate change projections indicate that over the coming decades the B.C. agricultural sector will have to deal with significantly changing conditions. B.C. producers will face increased management complexity, business costs, and uncertainty due to impacts such as drought, excess moisture, flood risk, and pests and diseases. There will also be an increase in growing days and opportunities for new crops. Successful adaptation will be required for the industry to manage the risks, take advantage of the opportunities, and maintain growth and profitability.